2013
DOI: 10.1038/srep01385
|View full text |Cite
|
Sign up to set email alerts
|

Thin single-wall BN-nanotubes formed inside carbon nanotubes

Abstract: We report a high yield synthesis of single-wall boron nitride nanotubes (SWBNNTs) inside single-wall carbon nanotubes (SWCNTs), a nano-templated reaction, using ammonia borane complexes (ABC) as a precursor. Transmission electron microscope (TEM), high angle annular dark field (HAADF)-scanning TEM (STEM), electron energy loss spectra (EELS) and high resolution EELS mapping using aberration-corrected TEM system clearly show the formation of thin SWBNNTs inside SWCNTs. We have found that the yield of the SWBNNT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 52 publications
1
58
0
Order By: Relevance
“…If the ammonium borane is heated with SWCNT, hexagonal BN nanotubes form inside the SWCNTs [18]. As estimated from these studies, the BN sheets become deposited on CNHs when they are heated with ammonia borane, evidence of which is shown below.…”
Section: Structure Analysis Of Bn-cnh Prepared At 800°cmentioning
confidence: 81%
See 2 more Smart Citations
“…If the ammonium borane is heated with SWCNT, hexagonal BN nanotubes form inside the SWCNTs [18]. As estimated from these studies, the BN sheets become deposited on CNHs when they are heated with ammonia borane, evidence of which is shown below.…”
Section: Structure Analysis Of Bn-cnh Prepared At 800°cmentioning
confidence: 81%
“…It has been reported that o-carborane can be incorporated inside SWCNTs [35], and BN tubes can be formed inside SWCNTs [18]. The attachment of boron compounds to the outside of carbon nanotubes has also been reported [11].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Over the past decade, the self-assembled systems [2,3] relied on the special hollow structure of cylindrical SWCNTs, are an attractive class of new bio-inspired nanomaterial for biologists and material scientists, because the self-assembled materials may not only be designed to be highly dynamic, displaying adaptive and self-healing properties, but could also help gain an understanding of the rules that govern biomolecule assembly processes [4]. In the self-assembly process, the hollow interior of SWCNT can serve as nanometre-sized moulds and templates [5] to control the configuration of other materials, or as a protective layer [6] to prevent the filler from oxidation and shape fragmentation. The physical and chemistry properties of the heterostructure are expected to be modified due to the interaction between SWCNT and exotic materials [7].…”
Section: Introductionmentioning
confidence: 99%
“…These considerable differences between the two nanotubes result in proposing hybrid carbon and boron nitride nanotubes since the earlier attempts of doping carbon nanotubes with boron and nitrogen [21] in order to overcome the drawbacks in applying the individual pure CNTs and BNNTs in novel applications. To this end, many efforts have been made to fabricate carbon and boron nitride hybrid nanotubes since 1994 [22][23][24][25][26][27][28][29]. Regarding the developments in experimental growth of hybrid nanotubes, several theoretical and experimental investigations have been carried out to explore the electromagnetic properties and stability of these hybrid nanotubes unlike the mechanical properties which are limited to elastic properties [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%